A novel spatial Tomlinson–Harashima precoding scheme in multi-user MIMO broadcast channels. (8th May 2012) - Zhang, Zufan; Yi, Yinxue; Yang, Jing
Spatial Tomlinson–Harashima Precoding (STHP) is a promising transmission technique that can mitigate Inter-User Interferences (IUI) in a multi-user Multiple Input Multiple Output broadcast channel. However, traditional STHPs cannot guarantee user fairness that is supposed to be a desirable feature for future wireless communication systems. This paper proposes an improved STHP transceiver structure. It is based on zero-forcing criterion and has the perfect user fairness. In addition to this, we also derive an elegant ordering method that can significantly improve the system performance.